Analysis of a photovoltaic unit using computational fluid dynamics - Fernandes, Gérson (2012)
The use of photovoltaic panels is rising, and its use will play a significant role in achieving the European Union’s target of 20% of energy consumption coming from renewable resources. At the same time, suppliers of solar energy panels aim to optimise the use of photovoltaic cells. This can be done, for example, by using intelligent methods of cooling to gain the maximum electrical output possible, and minimizing cost by reducing the number of cells without compromise in power output. WS Energia, a national market leader in solar technology, has developed proprietary solutions for the harvesting of solar energy. Computational fluid dynamics (CFD) is the method of solving of the Navier-Stokes equations at discrete points via a numerical method. The aim of this study is to use CFD to gain an insight of on two different levels of the photovoltaic unit. The first is to calculate the forces and induced vibrations on the structure with varying wind velocities and profiles. The second objective is to study the heat transfer mechanisms within the solar cell, in order to utilize innovative cooling methods to optimise the electrical output. Preliminary studies consisting of laminar flow in two dimensions have been conducted on a photovoltaic unit. The aim is to validate the computational setup and the turbulence modelling. This will be compared with data aquired in the experimental facilities of WS Energia. More comprehensive simulations are in progress. The commercial Navier-Stokes solver, Ansys Fluent will be used for this study in a newly acquired computational hardware.